2008
DOI: 10.1016/j.crci.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic adsorption onto hematite and goethite

Abstract: Surface complexation reactions on mineral affect the fate and the transport of arsenic in environmental systems and the global cycle of this element. In this work, the sorption of As(V) on two commercial iron oxides (hematite and goethite) was studied as a function of different physico-chemical parameters such as pH and ionic strength. The main trend observed in the variation of the arsenic sorbed with the pH is a strong retention in acidic pH and the decrease of the sorption on both sorbents at alkaline pH va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(87 citation statements)
references
References 24 publications
9
76
0
2
Order By: Relevance
“…Alumina has been found to effectively remove iAs V [55], but it is necessary to use activated alumina to efficiently remove iAs III from solution [56]. A multitude of studies on As adsorbents have been conducted using Fe-based mineral sorbents [57,58], such as magnetite [54,[59][60][61][62][63], ferrihydrite [53,54,[64][65][66], goethite [48,54,66,67], and zero-valent iron [62].…”
Section: Arsenic Treatment Methodsmentioning
confidence: 99%
“…Alumina has been found to effectively remove iAs V [55], but it is necessary to use activated alumina to efficiently remove iAs III from solution [56]. A multitude of studies on As adsorbents have been conducted using Fe-based mineral sorbents [57,58], such as magnetite [54,[59][60][61][62][63], ferrihydrite [53,54,[64][65][66], goethite [48,54,66,67], and zero-valent iron [62].…”
Section: Arsenic Treatment Methodsmentioning
confidence: 99%
“…They have been widely used in the extraction of heavy metals from natural [6] and industrial sources [7], which has generated a great number of studies about mechanisms of surface interactions [8][9][10][11][12]. These minerals are common in environments with high availability of metal sulphides exposed to oxidizing conditions, as in acid sulphate soils, in the oxidation zone of mine tailings, or ore deposits [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely distributed worldwide and found in abundance in numerous locations around the world (Encyclopedia Britannica 2014). Goethite has been studied as an absorbent for arsenic removal (Chakravarty et al 2002;Giménez et al 2007;Lakshmipathiraj et al 2006;Mamindy-Pajany et al 2009). Chakravarty et al (2002) reported it as ''major mineral phase'' in their ''low cost ferruginous manganese ore'' which achieved nearly 100 % As removal.…”
Section: Introductionmentioning
confidence: 99%